Effects of uranium mining on health: a case study of Jadugoda of Jharkhand, India - Koustab Majumdar; Lal Chhandama; Punam Kumari; Dipankar Chatterjee (Discover Global Society)
Abstract While the measurement of radiological risk and its environmental and ecological impacts has been extensively studied, the effects on human health particularly among populations living near mining areas have received comparatively less attention. In this context, the present study investigates the health impacts of uranium mining on residents living in close proximity to the Jadugoda uranium mining region in India. Drawing on in-depth interviews with 37 respondents and 4 health workers from three villages adjacent to the mining site, the study reveals a high prevalence of chronic health conditions. These include respiratory issues (such as bronchitis, chest pain, and chronic coughing), skin diseases, various forms of cancer, neuropsychiatric disorders, congenital disabilities (e.g., birth defects, developmental delays, and physical deformities), and reproductive health problems (such as irregular menstruation, excessive bleeding, urinary infections, and miscarriage). In addition to these physical ailments, participants reported severe psychological distress, including anxiety, fear, and suicidal ideation. According to community members, unprotected tailing ponds where mining waste is improperly stored are perceived as a primary source of radiological exposure. In light of these findings, the study calls for urgent public health interventions and further research into the long-term health consequences of uranium mining in affected regions. We recommend several key interventions including strengthening local healthcare systems, enforcing safe mining and waste management regulations, and regularly monitoring radiation levels. Financial support for affected individuals especially cancer patients and collaboration among public health agencies, local authorities, and civil society are essential for an effective response.